César Chávez : the struggle for justice = César Chávez : la lucha por la justicia - Griswold del Castillo, Richard (Hispanic civil rights series,, 2002)
A simple biography of the man who worked to win fairer treatment of the migrant farm workers in California in the 1960s and to establish the United Farm Workers union.